Cyclic di-AMP oversight of counter-ion osmolyte pools impacts intrinsic cefuroxime resistance in Lactococcus lactis - Pham, Huong Thi (2022)
The broadly conserved cyclic di-AMP (c-di-AMP) is a conditionally essential bacterial second messenger. The pool of c-di-AMP is fine-tuned through diadenylate cyclase and phosphodiesterase activities, and direct binding of c-di-AMP to proteins and riboswitches allows the regulation of a broad spectrum of cellular processes. c-di-AMP has a significant impact on intrinsic β-lactam antibiotic resistance in Gram-positive bacteria; however, the reason for this is currently unclear. In this work, genetic studies revealed that suppressor mutations that decrease the activity of the potassium (K+) importer KupB or the glutamine importer GlnPQ restore cefuroxime (CEF) resistance in diadenylate cyclase (cdaA) mutants of Lactococcus lactis Metabolite analyses showed that glutamine is imported by GlnPQ and then rapidly converted to glutamate, and GlnPQ mutations or c-di-AMP negatively affects the pools of the most abundant free amino acids (glutamate and aspartate) during growth. In a high-c-di-AMP mutant, GlnPQ activity could be increased by raising the internal K+ level through the overexpression of a c-di-AMP-insensitive KupB variant. These results demonstrate that c-di-AMP reduces GlnPQ activity and, therefore, the level of the major free anions in L. lactis through its inhibition of K+ import. Excessive ion accumulation in cdaA mutants results in greater spontaneous cell lysis under hypotonic conditions, while CEF-resistant suppressors exhibit reduced cell lysis and lower osmoresistance. This work demonstrates that the overaccumulation of major counter-ion osmolyte pools in c-di-AMP-defective mutants of L. lactis causes cefuroxime sensitivity.IMPORTANCE The bacterial second messenger cyclic di-AMP (c-di-AMP) is a global regulator of potassium homeostasis and compatible solute uptake in many Gram-positive bacteria, making it essential for osmoregulation. The role that c-di-AMP plays in β-lactam resistance, however, is unclear despite being first identified a decade ago. Here, we demonstrate that the overaccumulation of potassium or free amino acids leads to cefuroxime sensitivity in Lactococcus lactis mutants partially defective in c-di-AMP synthesis. It was shown that c-di-AMP negatively affects the levels of the most abundant free amino acids (glutamate and aspartate) in L. lactis Regulation of these major free anions was found to occur via the glutamine transporter GlnPQ, whose activity increased in response to intracellular potassium levels, which are under c-di-AMP control. Evidence is also presented showing that they are major osmolytes that enhance osmoresistance and cell lysis. The regulatory reach of c-di-AMP can be extended to include the main free anions in bacteria.